The interplay of Qur'ānic synonymy and polysemy with special reference to al-asfār and al-kutub (the books) and their English translations - Abdul-Qader Khaleel Mohammed Abdul-Ghafour,; Norsimah Mat Awal,; Intan Safinaz Zainudin,; Ashinida Aladdin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study investigates the meanings of the near-synonyms al-asfār and alkutub (the books) and their English translations. It aims at identifying the contextual meanings of the Qur'ānic near-synonyms based on different exegeses of the Holy Qur'ān. Then, it explains the semantic differences that exist between the Qur'ānic pair and how such semantic differences are reflected in two English translations of the Holy Qur'ān. Besides, it highlights the meanings of the polysemous lexical item alkutub (the books) in different Qur'ānic contexts and how the various senses of this lexical item are transferred to English. The study adopts the RC-S approach as a theoretical framework for data analysis. It also employs the qualitative approach for collecting and analyzing the data of the study. The exegeses of the Holy Qur'ān are consulted to identify the semantic differences between the Qur'ānic near-synonyms as well as the meanings of the polysemous lexical item alkutub (the books). The findings reveal that there are some semantic differences between the selected Qur'ānic near-synonyms and that such semantic differences are not reflected in the English translations. The findings also show that the polysemous lexical item alkutub (the books) and its singular formal-kitāb (the book) are literally translated in some Qur'ānic contexts. The study provides recommendations for readers as well as translators especially the translators of the Holy Qur'ān.